Toward Evidence Based Practice. Issue 2 (March 2015) - Woodgate, Roberta; Krowchuk, Heidi; Lewis, Judith A.
<x xml:space="preserve">Abstract</x> Experts suggest how 6 research articles can be used in nursing practice.